Improving community pharmacists' clinical knowledge to detect and resolve drug-related problems in Croatia: a before/after survey study investigating the efficacy of an educational intervention. Issue 6 (1st June 2020) - Zekan, Lovre; Mestrovic, Arijana; Perisin, Ana Seselja; Bukic, Josipa; Leskur, Dario; Rusic, Doris; Modun, Darko
Abstract : Objectives: The aim of this study was to increase the knowledge level of community pharmacists in Croatia to identify and resolve drug-related problems (DRPs). Design: Before/after survey study. Setting: University of Split School of Medicine. Participants: 115 community pharmacists from all over the Croatia. Interventions: An interactive 3-day clinical pharmacy workshop with the goal of increasing the knowledge level of community pharmacists in Croatia to identify and resolve DRPs in routine practice. Teaching methods were based on interactive clinical case solving. Outcome measure: Change of the community pharmacists' knowledge based on preworkshop and postworkshop evaluation. A survey-based clinical knowledge measurement tool was used in order to evaluate the efficacy of the workshop. The lowest possible total score was 0 and the highest was 80. A higher survey score indicates a higher level of clinical knowledge to identify and resolve DRPs. Results: Participating pharmacists had significantly higher postworkshop mean survey score (49.1±8.0) than the preworkshop mean survey score (42.9±8.2), with the mean score difference of 6.2 (95% CI 4.3 to 8.1). Furthermore, it was found that community pharmacists significantly increased their survey scores, regardless of their age. Conclusions: Interactive and case-based clinical pharmacy workshop could be a valuable tool to increase the knowledge of community pharmacists about identification and management of DRPs in routine practice. However, further studies are necessary to evaluate the long-term knowledge maintenance and the improvement in patients' clinical outcomes.